Modeling and Using Context 8th International and Interdisciplinary Conference, CONTEXT 2013, Annecy, France, October 28 - 31, 2013, Proceedings - Brézillon, Patrick.; Brézillon, Patrick.; Blackburn, Patrick.; Blackburn, Patrick.; Dapoigny, Richard.; Dapoigny, Richard. (Lecture Notes in Artificial Intelligence ;, 2013)
This book constitutes the proceedings of the 8th International and Interdisciplinary Conference on Modeling and Using Context, CONTEXT 2013, held in Annecy, France, in October/November 2013. The 23 full papers and 9 short papers presented were carefully reviewed and selected from numerous submissions. In addition the book contains two keynote speeches and 9 poster papers. They cover cutting-edge results from the wide range of disciplines concerned with context, including: Cognitive Sciences (Linguistics, Psychology, Computer Science, Neuroscience), and computer science (artificial intelligence, logics, ubiquitous and pervasive computing, context-awareness systems), and the Social Sciences and Organizational Sciences, as well as the Humanities and all application areas, including Medicine and Law.